Political Communication Strategy and Public Opinion for the Victory of the Prabowo Gibran Pair in the 2024 Presidential and Vice Presidential Elections of the Republic of Indonesia - Fardiansyah, Hardi; Euis Komalawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the context of a political communication strategy focused on the campaign for candidate pair number 2 Prabowo Subianto-Gibran Rakabuming Raka, this research shows that their communication strategy is very effective, especially among young voters. This research uses a qualitative approach with primary data in the form of interviews and documentation from various informants, such as TKN/Golkar/Partai Pengusung, TKN Secretary, as well as the community and volunteers who were randomly selected. The research results show the Prabowo-Gibran communication strategy. First, the Prabowo-Gibran candidate pair aims to convince the public, especially Generation Z, about their vision and mission as presidential candidates. This goal includes efforts to build a positive image, increase electability, and win the presidential election. Second, these candidate pairs use various persuasive communication strategies, such as creative and diverse campaigns, the use of social media to spread messages, and participation in debates to strengthen their arguments and vision. Third, the Prabowo-Gibran candidate pair targets Generation Z in particular as important potential voters, using language and communication platforms that suit Generation Z's preferences and habits to increase their appeal